2016
DOI: 10.3233/nua-150051
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of berry polyphenols against age-related cognitive impairment

Abstract: Abstract.A growing body of evidence suggests that dietary interventions may delay or halt the progression of age-related health disorders and cognitive decline. Among the components of the human diet, polyphenols from berries are essential micronutrients that have been particularly studied for improving cognitive functions. In the present review, we highlight the health impact of major polyphenolic classes found in berries: flavanols, anthocyanins and stilbenes, focusing on resveratrol. The reports of benefici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 203 publications
(189 reference statements)
1
32
0
Order By: Relevance
“…Actually, there is a growing interest in nutritional intervention studies to confirm the neuromodulatory role of polyphenols on brain health and function, as well as to sustain the idea of healthy brain aging (Bensalem et al 2015). At the same time, it is necessary to better define the metabolic profile, absorption profiles, and bioavailability of polyphenols to translate polyphenols-based therapeutic approach in AD animal models into a clinical therapeutic benefit (Mancuso et al, 1822;D' Archivio et al 2010).…”
Section: Grape Polyphenolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Actually, there is a growing interest in nutritional intervention studies to confirm the neuromodulatory role of polyphenols on brain health and function, as well as to sustain the idea of healthy brain aging (Bensalem et al 2015). At the same time, it is necessary to better define the metabolic profile, absorption profiles, and bioavailability of polyphenols to translate polyphenols-based therapeutic approach in AD animal models into a clinical therapeutic benefit (Mancuso et al, 1822;D' Archivio et al 2010).…”
Section: Grape Polyphenolsmentioning
confidence: 99%
“…However, further work is needed to better understand polyphenol absorption, metabolism, tissue distribution, intracellular accumulation and excretion, and brain bioavailability. Furthermore, the structural changes and chemical biotransformation of polyphenols during metabolism and interaction with the BBB within the target brain need more clarification to determine their cerebral bioavailability (Bensalem et al 2015). Actually, resolving the bioavailability of natural polyphenols is more challenging than with synthetic compounds (Rubio et al 2014), because resident gut microbiota generates secondary metabolites (Van Duynhoven et al 2011).…”
Section: Brain Localization and Bioavailability Of Polyphenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…[80] A large body of evidence speculates that PCs have protective effects against age-related degenerative diseases. [81] Animal studies and in vitro studies have generally reported the beneficial activities of PCs against HDs, but further explorations are still necessary to determine the accurate mode of action of PCs. The inconsistency between experimental studies and clinical studies may be partly due to the many technical problems with human studies.…”
Section: Link Between the Mechanism Of Action Of Pcs And Human Diseasesmentioning
confidence: 99%
“…Berries are both an enjoyable and important part of a balanced diet providing energy, nutrients and dietary fiber, and contain a large number of compounds showing diverse health-promoting activities in humans (Seeram, 2012;Nile and Park, 2014). Edible berry species contain a diverse and concentrated portfolio of (poly)phenols such as anthocyanins, flavanols (epicatechin), and stilbenes (resveratrol), which are known to confer protection against oxidative stress and to have cytoprotective activities (Rodriguez-Mateos et al, 2014;Bensalem et al, 2015). In recent years, there is increasing evidence that natural phenols in berry fruits also show protective effects against metabolic disorders such as diabetes and obesity and against neurodegenerative diseases (ND; Yang and Kortesniemi, 2015;Tsuda, 2016;Rosado-Ramos et al, 2018).…”
mentioning
confidence: 99%